2016
DOI: 10.1080/10454446.2016.1141143
|View full text |Cite
|
Sign up to set email alerts
|

Food for Kids: How Children Influence their Parents Purchasing Decisions

Abstract: During the last decades, sociological changes have modified the role of children within families: participatory models have become more widespread, to the detriment of more author- itative ones: this change has had consequences also in refer- ence to families’ purchases. In scientific literature some scholars have shown that this influence is real, and marketers try to take advantage of this through a communication style that attempts to “teach” children how to pester their parents: this is the so-called nag f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 21 publications
1
21
0
1
Order By: Relevance
“… 33 Children influence the purchasing decisions of their parents, but this influence decreases when parents become more aware of the importance of a healthy diet. 34 …”
Section: Discussionmentioning
confidence: 99%
“… 33 Children influence the purchasing decisions of their parents, but this influence decreases when parents become more aware of the importance of a healthy diet. 34 …”
Section: Discussionmentioning
confidence: 99%
“…15 Such product preferences can lead to increased "pester power," in which children beg parents for specific products or brands. [16][17][18][19][20] In fact, pester power results in $190 billion in sales each year. 21 Second, children ages #8 years have limited cognitive abilities to recognize advertising.…”
mentioning
confidence: 99%
“…Researchers have demonstrated that children impact their parents' purchasing decisions (Baldassarre, Campo, & Falcone, 2016;Nicholls & Cullen, 2004;Wilson & Wood, 2004) and the values or attitude of their parents (Dillon, 2002). If children have more knowledge of a product, they could exert more influence on parents' purchase decision for that product (Thomson, Laing, & McKlee, 2007).…”
Section: Upward Intergenerational Influences On Innovativenessmentioning
confidence: 99%